2019
DOI: 10.1016/j.redox.2018.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Persistent increase in mitochondrial superoxide mediates cisplatin-induced chronic kidney disease

Abstract: Severe and recurrent cisplatin-induced acute kidney injury (AKI) as part of standard cancer therapy is a known risk factor for development of chronic kidney disease (CKD). The specific role of superoxide (O2•-)-mediated disruption of mitochondrial oxidative metabolism in CKD after cisplatin treatment is unexplored. Cisplatin is typically administered in weekly or tri-weekly cycles as part of standard cancer therapy. To investigate the role of O2•- in predisposing patients to future renal injury and in CKD, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 50 publications
1
82
0
Order By: Relevance
“…It is generally accepted that the development and progression of both acute and chronic kidney diseases may be primarily attributed to the imbalanced molecular mechanisms that govern oxidative stress [50]. The superoxide anions-mediated renal tubules damage may be an important contributor to the progression of AKI [51]. In light of oxidative stress, salusin-β is recently proposed as an oxidation inducer in brain tissues, VSMCs and endothelial cells in multiple disease scenarios [23,28,52].…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that the development and progression of both acute and chronic kidney diseases may be primarily attributed to the imbalanced molecular mechanisms that govern oxidative stress [50]. The superoxide anions-mediated renal tubules damage may be an important contributor to the progression of AKI [51]. In light of oxidative stress, salusin-β is recently proposed as an oxidation inducer in brain tissues, VSMCs and endothelial cells in multiple disease scenarios [23,28,52].…”
Section: Resultsmentioning
confidence: 99%
“…Following renal uptake, cisplatin in the cytoplasm is hydrolyzed into a positively charged electrophile that can accumulate within the negatively charged mitochondrial membrane and disrupt its membrane potential [46]. This, in turn, induces superoxide generation by negatively affecting mitochondrial metabolism, the efficiency of the ETC, and ATP production [47]. Cisplatin-induced nephrotoxicity is also associated with increased DRP1-mediated mitochondrial fragmentation, cytochrome c release, apoptosis of proximal tubular cells, and renal injury [38].…”
Section: Cisplatin-induced Akimentioning
confidence: 99%
“…In cisplatin-associated AKI, mitochondrial dysfunction associated oxidative stress leads to intracellular reactive oxygen species (ROS) accumulation. Previous research showed that cisplatin administration is followed by increased oxidative stress levels and alteration in the expression of various antioxidant enzymes [96,97,98]. Mitochondria is the home of the cellular ATP synthesis and the main source of ROS production.…”
Section: Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%